Dinar Candy, pornography, freedom of expression, and the law - Sujana Donandi S (Jurnal Cakrawala Hukum, 2022)
Dinar Candy expressed her feeling to PPKM by wearing bikini in the road-side which caused her be stipulated as the suspect of pornography. Dinar Candy’s case brought to the conception on the limitation of pornography interpretation and the determination on freedom of expression in action of wearing bikini. The research is conducted through a qualitative approach using secondary data. The results show, first: pornography is limited by ‘subjective reason’ such as if the pornography is aimed for personal interest, then the action is not pornography. The other is ‘action-room limitation’ in which an action can be formulated as pornography if the standard and characteristic in the room where the action is done considering that the action is obscene or aims to sexual exploitation. The room refers to specific places such as beach, roadside, hotel, or other specific place, not wide social room. Second: If someone’s feeling is expressed by wearing bikini in a room which based on its decency standard allows to wear bikini, then the action can be determined as freedom of expression. In contrary, in a room where bikini is considered against morality, or it is spread to public, then such action is against the pornography law.How to cite item: Donandi S, S. (2022). Dinar Candy, pornography, freedom of expression, and the law. Jurnal Cakrawala Hukum, 13(2), 202-213. DOI:https://doi.org/10.26905/idjch.v13i2.6517.